KARAKTERISTIK SUSUT MASAK DAN HEDONIK SOSIS DAGING DADA DAN PAHA KALKUN (Meleagris gallopavo) - Robby Rusdiansyah; Bambang Dwiloka; Yoyok Budi Pramono (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2021)
This study aims to determine the differences in the quality of cooking and hedonic losses based on commercial cuts of the carcass. The benefit of this research is to increase the diversification of food products based on turkey livestock and to obtain information regarding the different treatment of commercial carcass cuts on the quality of processed turkey meat. The experimental design used was a randomized block design (RBD) with 2 treatments of commercial pieces of carcass and thighs with 4 repetitions. The treatments given were (T1) breast meat and (T2) thigh meat. The parameters tested were cooking and hedonic losses which consisted of taste, aroma, color, texture, and overall. The results showed that the commercial cut of the carcass affected showing differences in the quality of cooking loss and hedonic quality of turkey sausage. Panelists liked the commercial cut sausages of breast carcass and gave the result that breast treatment could reduce cooking losses and thus increase the economic value of the product.